Impact of PLAI conferences, etc. to the professional development of librarians and information professionals, 1991-1995 - Villanueva, Aloha O. (Institute of Library Science, University of the Philippines Diliman, 1997)
This study was conducted to find out if conferences, seminar-workshops, lecture-forums and other activities sponsored by the PLAI (Philippine Librarians Association, Inc.) from 1991 had any impact on the professional development of its members.